Examining the Denotation of the Principle, “Necessity of Abstention…” for Divorce in Case of Avoidance or Inability of the Husband in Fulfilling Marital Rights - ?????, ???????; ?????, ??? ????; ??? ?????, ?? ??????; ????????, ????? (??? ? ????)
The fact that divorce is a right, vindication of which is legally granted to men and which the Iranian civil law has asserted in article 1133, is on the condition that man’s relation to the woman follows its natural procedure. In case there is a man who would neither fulfill marital duties nor consent to divorce, then what is to be one? Does the woman have to tolerate her husband’s transgression till the end of her life? In this case, can a judgment be made obligating the husband to divorce her with reliance on the rule, “Necessity of abstention by virtue and repudiation by benevolence”? Is the above principle also applicable to the case in which the husband’s evading his marital duties is out of impotence and disability? Using the analytical-descriptive method, this article is intended to find answers to these questions. With a survey of the jurists’ various viewpoints, the conclusion is made that the principle denotes that in married life, it is necessary for the husband to choose one of the following two ways toward his wife: either fulfill all rights and duties in a properly and competent way or leave her. This principle is general and comprises all the wife’s rights and there is no difference between the husband’s voluntary or natural shortcoming.